Anayasa Hukuku ve Şiddet - (:unkn) unknown (My University, 2016)
Şiddetten korunma ihtiyacı öncelikle devletin temellendirilmesinde kullanılmıştır. Şiddet, anayasaların yapılmasıyla da doğrudan ilgilidir. Ayrıca anayasalar çoğu durumda olağanüstü dönemlerin hukukunu düzenler. "Meşru şiddet kullanma tekeline sahip olan" tek insan örgütlenmesi olarak devlet, bir de egemenlik boyutuyla karşımıza çıkar. Anayasa aynı zamanda devletin hukuksuz şiddetini kontrol altına almaya yönelik bir metindir. Anayasa hukuku belli haller dışında açıkça bireyler arası şiddeti düzenlemez. Ancak bu dalın şiddetin hukukunu düzenleyişi daha çok devletin sosyal ve ekonomik alandaki yükümlülükleri ile somutlaştırılabilir. Başka bir deyişle, Anayasada yer alan "sosyal devlet", "devletin temel amaç ve görevleri" ve bazı temel hak düzenlemeleri devlete bireyler arasındaki ilişkilerde bir takım koruma yükümlülükleri yüklemektedir.

The need to protection from violence is used primarily in the state construction. Traditionally the violence appears as one of the distinctive features of constitutional moments. The Constitutions also contain the emergency clauses. Furthermore, the state as being the sole power which has the monopoly of violence possesses the sovereignty. The essential objective of the constitutionalism is the control of the governmental actions. Hence the constitution tends to control the illegal state violence as well. Principally, constitutional law does not regulate explicitly the violence between individuals except below-mentioned dispositions. However, the state having positive obligations with regard to eliminate the violence in the social and economic sphere is not except from constitutional responsibilities in this respect. In other words, the dispositions relating to "social state", "principal duties of state" and certain fundamental rights are the implicit constitutional basis for the protection from violence.
(Constitutional Law and Violence)
Keywords: Tarih; Uluslararası İlişkiler; Hukuk; Siyasi Bilimler; Sosyal Çalışma